The Application of Transition Metal Nitride Catalyst in the HDO Reaction of Lignin and Its Model Compounds - Chang Sok Kim; Jong Nam Kim; Hak Myong Song; Hyon Il Do; Se Kwon O (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
As the only abundant and renewable non-fossil resource that provides aromatic compounds in nature, lignin is an important raw material for the production of new energy and high-value chemicals. Transition metal nitride is widely used as a good hydrodeoxygenation (HDO) catalyst in the catalytic conversion reaction of lignin and its model compounds thanks to its crystal structure and properties, and good hydrodeoxygenation activity similar to noble metals. This paper reviewed the application of transition metal nitride catalysts in catalytic conversion of lignin and its model compounds. And the paper comprehensively analyzed the components of transition metal nitride catalyst, the nitriding method and the molar hourly space velocities (MHSV) in the preparation process, the carrier, the addition of other metals, the influence of reaction conditions on the catalytic activity and the reaction mechanism. In addition, the paper discussed the problems arising in applying the transition metal nitride catalysts in the reaction of lignin and its model compound HDO were proposed, and proposed the ways to develop nitride catalysts with higher catalytic performance and wider application prospect. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).